The relationship between dietary inflammation potential, dietary oxidative balance score, and female reproductive function: a mediation analysis of obesity indicators - Mingyue Liang; Mingyue Liang; Mingyue Liang; Xuanhui Wu; Xuanhui Wu; Xuanhui Wu; Ying Xie; Ying Xie; Ying Wang; Ying Wang; Ying Wang; Bin Luo; et al. (Frontiers in Endocrinology)
BackgroundDietary inflammation and oxidative stress have been linked to reproductive health, and weight gain has also been found to play an important role in female reproductive function specifically. In this study we explore the effects of dietary inflammatory index (DII) and dietary oxidative balance score (DOBS) on infertility and sex hormones, and clarify the mediating role of obesity on these effects.MethodsA total of 1,774 subjects from the 2013-2016 National Health and Nutrition Examination Survey (NHANES) were selected. The DII and DOBS were determined by aggregating data on 26 and 17 dietary components obtained by dietary recall, respectively. Infertility (yes or no, self-reported in questionnaire) and serum gonadal hormones including total testosterone (TT), estradiol (E2), and sex hormone-binding globulin (SHBG) were considered as main outcome variables. Multivariate logistic regression and restricted cubic splines (RCS) were applied for further analysis, and mediation models were constructed to figure out the mediating role of obesity indicators.ResultsThe prevalence of infertility among American women of childbearing age was 12.66%. There were significant linear relationships between the DII and DOBS, and infertility and serum SHBG (p for overall < 0.05). Consuming foods with higher DII was significantly associated with higher risk of infertility (OR: 1.86; 95% CI: 1.20-2.89) and lower levels of SHBG (β: -9.98; 95% CI: -19.45–0.51). Compared to the lowest DOBS category, the adjusted beta estimates for SHBG and E2 were 12.03 (95% CI: 2.01-22.04) and 134.58 (95% CI: 3.46-266.24) in the highest DOBS group. However, anti-inflammatory and anti-oxidative diets reduced the risk of infertility by 51% and increased SHBG levels by 14.54 nmol/L. Interestingly, obesity indicators mediated the associations of dietary inflammation and oxidative stress potential with infertility and SHBG.ConclusionsDietary inflammation and oxidative stress are strongly associated with the risk of infertility and serum SHBG levels, indicating that anti-inflammatory and anti-oxidative diets may mitigate fertility disorders that result from obesity.